2015
DOI: 10.1021/jacs.5b09980
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed Enantioselective Allylic Substitution of Enol Silanes from Vinylogous Esters and Amides

Abstract: The enol silanes of vinylogous esters and amides are classic dienes for Diels–Alder reactions. Here, we report their reactivity as nucleophiles in Ir-catalyzed, enantioselective allylic substitution reactions. A variety of allylic carbonates react with these nucleophiles to give allylated products in good yields with high enantioselectivities and excellent branched-to-linear ratios. These reactions occur with KF or alkoxide as the additive, but mechanistic studies suggest that these additives do not activate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 117 publications
(44 reference statements)
0
25
0
3
Order By: Relevance
“…We began our studies on the enantioselective allylic substitution of aliphatic silyl ketene acetals by examining the reaction between cinnamyl methyl carbonate and ketene acetal 2 a in the presence of a series of metallacyclic iridium complexes containing various aryl substituents on the chiral ligand (Table , entry 1–4). A catalytic amount of tetrabutylammonium acetate ( n Bu 4 NOAc) was added to activate the silicon enolate because our previous studies demonstrated that carboxylates could activate silyl enol ethers in related iridium‐catalyzed allylation reactions . The reaction conducted with iridium catalyst [Ir]‐2 bearing two 2‐anisyl substituents on the ligand gave the ester product 3 aa in 50 % yield with >20:1 branched/linear selectivity and 98 % ee .…”
Section: Methodsmentioning
confidence: 99%
“…We began our studies on the enantioselective allylic substitution of aliphatic silyl ketene acetals by examining the reaction between cinnamyl methyl carbonate and ketene acetal 2 a in the presence of a series of metallacyclic iridium complexes containing various aryl substituents on the chiral ligand (Table , entry 1–4). A catalytic amount of tetrabutylammonium acetate ( n Bu 4 NOAc) was added to activate the silicon enolate because our previous studies demonstrated that carboxylates could activate silyl enol ethers in related iridium‐catalyzed allylation reactions . The reaction conducted with iridium catalyst [Ir]‐2 bearing two 2‐anisyl substituents on the ligand gave the ester product 3 aa in 50 % yield with >20:1 branched/linear selectivity and 98 % ee .…”
Section: Methodsmentioning
confidence: 99%
“…The enantioselectivity of the AAA reaction is known 53,56,[64][65][66][67][68] to be influenced by base choice or loading and therefore was also investigated by changing these two parameters in an AAA test reaction with 1 as the ligand ( Table 1). The potassium carbonate loading did not alter the enantioselectivity of reaction ( Table 1, Entries 1-3).…”
Section: Pd-catalyzed Asymmetric Allylic Substitution: Suppression mentioning
confidence: 99%
“…[11][12][13][14] In ersten Experimenten wurden verschiedene Iridacyclen C1-C5 [15,16] mit dem Dibenzocyclooctatetraen(dbcot)-Liganden in der Modellreaktion von Isoxazolinon 1a mit dem verzweigten racemischen allylischen Carbonat 2A in 1,2-Dichlorethan (DCE) bei 50 8 8Cu ntersucht (Tabelle 1, Nr. Letzteres war ursprünglich unerwartet, da Iridium-Phosphoramidit-Katalysatoren fürd ie Synthese von verzweigten allylierten Produkten mit einem sehr hohen Grad an Regioselektivitätb ekannt sind (Schema 1, Mitte).…”
unclassified
“…[4,8] Mit den Katalysatoren C1-C5 wurde ausschließlich das Callylierte Regioisomer gebildet. [12][13][14]. Während Iridacyclus C5 die hçchste Ausbeute lieferte (Nr.…”
unclassified
See 1 more Smart Citation